Doping of carbon nanodots for saving cells from silver nanotoxicity: A study on recovering osteogenic differentiation potential. (June 2019) - Das, Bodhisatwa; Dadhich, Prabhash; Pal, Pallabi; Dutta, Joy; Srivas, Pavan Kumar; Dutta, Abir; Mohapatra, Pradeep Kumar Das; Maity, Ananda Mukul; Bera, Sutanuka; Dhara, Santanu
Abstract: Silver nanoparticles are explored for many advanced biological applications including the development of antimicrobial surfaces on implants, SERS imaging, nanotherapeutics, biosensing and much more. However, recent research findings suggest silver nanoparticles provide blockade of differentiation of mesenchymal stem cells (MSCs), especially into osteogenic developmental pathway via generation of reactive oxygen species. These studies suggest that the application of silver nanoparticles in medical implants should be prohibited. In the current study, carbon nanodots (CND) supported silver clusters (AgC) is explored as a remedy to this problem. The nanostructure was synthesized in microwave irradiation induced rapid method and characterization was conducted via UV–Vis spectroscopy, fluorescence spectroscopy, HRTEM, XRD, FTIR, Raman spectroscopy, DLS, AFM, and XPS. Fluorescence spectrum showed a quantum yield of 0.25 while Raman spectroscopy showed rapid amplification of CND specific peaks implicating significant SERS property. Further in vitro biocompatibility (MTT) and bio-imaging capability was assessed culturing Wharton's Jelly-derived MSCs. In this study, its efficacy as in-situ cellular oxidative stress scavenger is also studied using NBT and DCFH-DA assay. Via ALP assay, alizarin red staining, cell membrane nanoindentation studies, PCR analysis and immunocytochemistry for osteoblast-like gene expression it was confirmed that AgCs can control silver nanoparticle-induced inhibition of osteogenic differentiation in vitro. Thus, AgCs (Carbon nanodots supported silver clusters) are not only considered to be a dual-mode bio-imaging nanoprobe but also a remedy to the silver-induced ROS generation and osteogenic differentiation blockade of MSCs. Highlights: Silver nanoparticles induce ROS mediated nanotoxicity. The ROS blocks osteogenic differentiation of MSCs. Carbon nanodots can scavenge ROS in situ. Doping silver nanoparticles in carbon nanodots reduce ROS production and recovers osteogenic differentiation.